Simulation of reference crop evapotransiration in a plastic solar green house using a simplified energy balance approach - Liu, X.F.; Liu, Z.G.; Duan, A.W.; Sun, J.S.; Liu, H.; Chen, Z.F.; Zhang, J.Y.; Shen, X.J.; Adaobi, U.P.; Uzokwe, Veronica N.E. (2015)
With larger planting areas being used in greenhouses, evaluating crop evapotranspiration in a greenhouse has garnered greater attention. Currently, calculating the reference crop evapotranspiration for a greenhouse crop through using the Penman-Monteith formula recommended by FAO is difficult because the wind speed in a greenhouse is approximate zero. In order to calculate reference crop evapotranspiration in a greenhouse by the Penman-Monteith modified formula, a simplified model for calculating reference crop evapotranspiration in a greenhouse was proposed based on the energy balance equation, which was the correlative function between reference crop evapotranspiration and radiation and temperature. The model's parameters were obtained through meteorological data taken from the inside of a greenhouse in 2011. Then, the model was validated by using meteorological data within the greenhouse in 2012, and the fitted value of the model agreed with the calculated value of the formulas with a determination coefficient (R2) of 0.9554. This model is an easy means of calculating the reference crop evapotranspiration in a greenhouse because less meteorological factors are needed. Furthermore, the model provides a theoretical basis for crop irrigation in greenhouses.